Ictus Emeticus Induced by Photic Stimulation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Occipitotemporal seizures induced by intermittent photic stimulation in three children with brain injuries, aged 10 to 13 years, are reported from the Institute of Developmental Neuropsychiatry, University of Pisa, Italy.